1970
DOI: 10.1063/1.1673544
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Metal Atoms. II. The Combination of Mercury and Bromine Atoms and the Dimerization of HgBr

Abstract: The combination reaction of mercury atoms with bromine atoms from the direct photolysis of CF3Br has been studied. The kinetics were followed by monitoring the band intensities of the Π3/2−22Σ and Π1/2−22Σ systems of the HgBr transient with kinetic absorption spectroscopy. The Π1/2−22Σ system has been analyzed and the following constants obtained: Te = 34 741 cm−1, ωe″ = 188 cm−1, and ωe′ = 274 cm−1. The extinction coefficient of the 2875-Å band of the Π1/2−22Σ system has been found to have the value 1.2 × 104… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

1977
1977
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 2 publications
2
14
0
2
Order By: Relevance
“…However, there could also be direct temperature effects in the reactions that oxidize GEM to reactive gas phase mercury (RGM). While experiments in the temperature range 393-448 K showed no temperature dependence of the oxidation of GEM by Br radicals (Grieg et al, 1970), similar studies at the low temperatures seen in the Arctic springtime (e.g. 230-273 K) are lacking, and theoretical calculations of the reaction rate predict an inverse temperature dependence (Goodsite et al, 2004), in qualitative agreement with the correlation reported here.…”
Section: Correlations Of Depletion and Emission Events With Meteorolosupporting
confidence: 78%
“…However, there could also be direct temperature effects in the reactions that oxidize GEM to reactive gas phase mercury (RGM). While experiments in the temperature range 393-448 K showed no temperature dependence of the oxidation of GEM by Br radicals (Grieg et al, 1970), similar studies at the low temperatures seen in the Arctic springtime (e.g. 230-273 K) are lacking, and theoretical calculations of the reaction rate predict an inverse temperature dependence (Goodsite et al, 2004), in qualitative agreement with the correlation reported here.…”
Section: Correlations Of Depletion and Emission Events With Meteorolosupporting
confidence: 78%
“…O 2 and NO accomplish oxidation to stable Hg II molecules: During AMDEs, BrO is demonstrated as a major candidate to participate in reaction . However, its viability to initiate oxidation is debated. ,, In addition to Br, ,,, atomic chlorine is a potent oxidant of Hg 0 ,, while the rate of the reaction between Hg 0 and I • is orders of magnitude lower and HgI is the weakest bound of the HgX molecules . In turn, the direct oxidation of Hg 0 by the free halogens (X 2 = Cl 2 and Br 2 ) viable through the insertion reaction Hg + X 2 → XHgX is strongly exothermic but nevertheless slow under atmospheric conditions due to large reaction barriers, whereas the abstraction Hg + X 2 → • HgX + X • proceeds only with significant rate at high-temperature conditions .…”
Section: Introductionmentioning
confidence: 99%
“…However, X 2 is an eminent scavenger of HgX , via Albeit the fast kinetics observed in the Hg 0 + Cl • reaction, it is not considered as an important sink for Hg 0 in the atmosphere due to the low estimated mean Cl • concentrations . The HgX radical–radical recombination yielding semivolatile Hg 2 X 2 is a fast reaction ,, but has no importance whatsoever in ambient air due to low atmospheric • HgX concentrations. However, reaction may at certain laboratory experimental conditions ,, be a substantial sink of • HgX in competition with reactions and .…”
Section: Introductionmentioning
confidence: 99%
“…Οι θεωρητικοί υπολογισμοί του Wadt(1980) Ashmore (1986) To σήμα φθορισμού που ανιχνεύεται στην περιοχή των 275-290 nm προέρχεται από την ηλεκτρονιακή μετάβαση C 2 Πι/2 -» Χ 2 Σι/2 του HgBr (Tellinghuisen 1983, Rai 1983, Ashmore 1986. Οι φασματοσκοπικές παράμετροι αυτής της μετάβασης έχουν μελετηθεί λεπτομερώς από φάσματα απορρόφησης (Grieg 1970) και από φάσματα εκπομπής (Rai 1983, Ashmore 1986. Οι διακριτές κορυφές που ανιχνεύθηκαν και η ταυτοποίηση τους σύμφωνα με τη δονητική ανάλυση του Rai (1983) φαίνονται στον πίνακα V-3.…”
Section: πειραματική διάταξηunclassified
“…Οι αντιδράσεις που είναι δυνατό να συμβούν μέσα στο κελί μεταξύ των ατόμων Hg, Br και των θραυσμάτων HgBr καθώς και οι αντίστοιχοι ρυθμοί φαίνονται στον Πίνακα V-5. Επίσης σε μελέτες χημειοφωταύγειας με μοριακή δέσμη (Hayashi 1977) Grieg (1970) Grieg (1970) Schilowitz (1982) Erlandson (1983 Από τον πίνακα V-5 φαίνεται ότι ο ρυθμός αναγέννησης του HgBr2 είναι ο ταχύτερος απ' όλες τις παραπάνω δυνατές αντιδράσεις, ο δε ρυθμός δέσμευσης των ατόμων του Hg από ελεύθερα άτομα Br είναι αρκετά αργός.…”
Section: μηχανισμοί απωλειών των ατόμων του Hg και διαδικασία σχηματισμού Hg2unclassified